Maresía : un viaje de Octavio & Dani (Proyecto Islas Canarias Colectivo Independiente, 2015)
Two young men travel on a 40-day caravan journey through the Canarian archipelago in order to re-discover their land, revalue their culture and bring a new point of view of the islands.--